An in-vitro and in Silico Anticancer Study of FDA Approved Antidiabetic Drugs Glimepiride and Empagliflozin: Life Sciences-Biochemistry for better diagnosis and therapy - Uzma Faridi; Fahad Al-Mutairi; Humaira Parveen; Sahar Khateeb (International Journal of Life Science and Pharma Research, 2022)
Drug repurposing is the way to find the role of the drug for new disease. Mostly the drug already passes human trails and approved by FDA. Many studies confirmed the role of many drugs in the treatment of more than one disease. Present research was conducted to evaluate the anticancer potential of FDA approved antidiabetic drugs Glimepiride and Empagliflozin. Glimepiride binds to ATP-sensitive potassium channel receptors and reduces the potassium conductance and Empagliflozin is a sodium glucose co-transporter-2 (SGLT-2) inhibitor. As many anti-diabetic drugs like meantime proved to be good anticancer drug so these two drugs were selected for the present study as their pharmacodynamics and pharmacokinetics studies are already reported and both showed no side-effect in human. The purpose of this study was to repurpose the Glimepiride and Empagliflozin as anticancer agents. In-vitro anticancer study was performed on two human cancer cell-lines MCF-7 and A549. To confirm the anticancer potential, the effect of these drugs on selected apoptotic proteins was studied in-silico. Both Glimepiride and Empagliflozin have significant anticancer activity on both the cell-lines but Empagliflozin seems to have better activity in-vitro. In-silico results indicated that both the drugs have significantly high activity towards apoptotic proteins. Although both the drug showed promising results in in-vitro and in-silico studies but the further studies like in-vivo studies are also required to prove these drugs as anticancer as well.